ANALYSIS OF THE INFLUENCE OF INTELLECTUAL CAPITAL AND CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE - Partogian Sormin; Claudia Cindy Manona (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
This study aims to examine and analyze the effect of intellectual capital and corporate governance on financial performance. This paper presents a new spectrum and recommendation to stakeholders. Previous research related to this already exists, but however, the results are not consistent. This study uses a method developed by Public, namely Value Added Intellectual Capital Efficiency , as an indicator for measuring intellectual capital, and uses three indicators of corporate governance, namely managerial ownership, proportion of independent commissioners, and proportion of independent audit committee. The sample used in this study were 28 manufacturing companies in the consumer goods industry sector listed on the IDX for the 2015-2019 period. The results of this study indicate that intellectual capital and the proportion of independent commissioners have a positive and significant effect on the company's financial performance; managerial ownership has a negative and significant effect on the company's financial performance; and the proportion of independent audit committee has a positive effect on the company's financial performance, but the effect is not significant.